Performance study of acrylonitrile butadiene rubber (nbr) latex/ eggshell filler composite film - Kathirayson, Kuhathason (2019)
The primary objective of this research is to produce acrylonitrile butadiene rubber (NBR)/ Eggshell Powder (ESP) composite film through the latex compounding and curing method. ESP loadings was varied from 0, 2, 4 to 6 phr to validate the effect of filler loading on the properties of the film. The composite films were cured at 80 oC for 120 minutes. All the composite film exhibit superior tensile strength, Young Modulus and elongation at break compared to pure NBR film, with optimum value at 4 phr loading. The dispersion of ESP in the tensile fracture was homogenous with no agglomeration observed. Resistance to chemical degradation and swelling increased with increment of filler loading. Crosslink density result showed that the higher loading of ESP filler, the crosslinking formation increased. The finding proves that ESP has a large potential to be used as a filler in latex film.